Synaptic inhibition in the olfactory bulb accelerates odor discrimination in mice - Abraham, Nixon M.; Egger, Veronica; Shimshek, Derya R.; Renden, Robert; Fukunaga, Izumi; Sprengel, Rolf; Seeburg, Peter H.; Klugmann, Matthias; Margrie, Troy W.; Schaefer, Andreas T.; Kuner, Thomas (Neuron, 2010)
Local inhibitory circuits are thought to shape neuronal information processing in the central nervous system, but it remains unclear how specific properties of inhibitory neuronal interactions translate into behavioral performance. In the olfactory bulb, inhibition of mitral/tufted cells via granule cells may contribute to odor discrimination behavior by refining neuronal representations of odors. Here we show that selective deletion of the AMPA receptor subunit GluA2 in granule cells boosted synaptic Ca2+ influx, increasing inhibition of mitral cells. On a behavioral level, discrimination of similar odor mixtures was accelerated while leaving learning and memory unaffected. In contrast, selective removal of NMDA receptors in granule cells slowed discrimination of similar odors. Our results demonstrate that inhibition of mitral cells controlled by granule cell glutamate receptors results in fast and accurate discrimination of similar odors. Thus, spatiotemporally defined molecular perturbations of olfactory bulb granule cells directly link stimulus similarity, neuronal processing time, and discrimination behavior to synaptic inhibition.